2011
DOI: 10.1186/1029-242x-2011-130
|View full text |Cite
|
Sign up to set email alerts
|

Refinements of Jordan's inequality

Abstract: A method of sharpening Jordan's inequality proposed by Li-Li would be improved. Increasing lower bounds and decreasing upper bounds for strengthened Jordan's inequality can be constructed and the errors of lower-upper bounds for strengthened Jordan's inequality can be estimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…M.-K. Kuo [117] has developed a method of obtaining an increasing sequence of lower bounds and a decreasing sequence of upper bounds for (sin x)/x, and he has conjectured that the two sequences converge uniformly to (sin x)/x.…”
Section: Generalizations Of Jordan's Inequalitymentioning
confidence: 99%
See 1 more Smart Citation
“…M.-K. Kuo [117] has developed a method of obtaining an increasing sequence of lower bounds and a decreasing sequence of upper bounds for (sin x)/x, and he has conjectured that the two sequences converge uniformly to (sin x)/x.…”
Section: Generalizations Of Jordan's Inequalitymentioning
confidence: 99%
“…They also found a method for obtaining new bounds from old for (sin x)/x, but M.-K. Kuo [117] gave an example to show that the new bounds are not necessarily stronger. In 2003 C.-P. Chen et al [77], using mathematical induction and infinite products, found analogs of the Redheffer inequality for cos x:…”
Section: Redheffermentioning
confidence: 99%
“…has been studied in a large number of literature works, and many refinements have been presented [1][2][3][4][5][6]. Zhang et al [7] gave the polynomial bounds of degree one:…”
Section: Introductionmentioning
confidence: 99%
“…The Jordan's inequality plays an important role in many areas of pure and applied mathematics. Many improvements and refinements of Jordan's inequality were presented in the recent period [2][3][4][5][6][7]. There are some sharp lower and upper bounds for the sinc(x) function by using polynomial degrees from 1 to 4.…”
Section: Introductionmentioning
confidence: 99%